2020
DOI: 10.3390/cancers12020331
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab and Its Derived EGFR Aptamer-Based Conjugate Induce Efficient NK Cell Activation against Cancer Cells

Abstract: The immune checkpoint CTLA-4 (cytotoxic T-lymphocyte-antigen 4), which inhibits the co-stimulatory CD28 signal on T cells, has been recently found expressed on other cell populations, such as tumor and natural killer (NK) cells. We tested for the first time the effects of ipilimumab, the human anti-CTLA4 mAb in clinical use, on these cells and found that it inhibits the growth of tumor cells expressing CTLA-4 also in the absence of lymphocytes, and efficiently activates NK cells, thus suggesting an important u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors. However, in line with other similar papers published in the literature [ 61 , 62 , 63 , 64 ], for all tested combinations (in our case controls and treatments with ipilimumab under high glucose and low glucose) the differences between groups are still due to the treatment conditions. Moreover, different open discussion papers are available about the role, for example, of HLA-E in co-cultures of cancer cells and PBMCs [ 68 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors. However, in line with other similar papers published in the literature [ 61 , 62 , 63 , 64 ], for all tested combinations (in our case controls and treatments with ipilimumab under high glucose and low glucose) the differences between groups are still due to the treatment conditions. Moreover, different open discussion papers are available about the role, for example, of HLA-E in co-cultures of cancer cells and PBMCs [ 68 ].…”
Section: Discussionsupporting
confidence: 89%
“…There are some limitations of this study: firstly, human leukocyte antigen (HLA)-class I molecules on tumor cells have been regarded as crucial sites where cytotoxic T lymphocytes can recognize tumor-specific antigens. HLA mismatch could be a possible limitation of co-cultures of tumor cells with hPMBCs, despite co-culture models often being used and recommended in preliminary cell-lymphocytes interaction studies, as reported in the literature [ 61 , 62 , 63 , 64 ]. Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma patients treated with anti-CTLA-4, a higher percentage of circulating mature NK cells is correlated with improved overall survival, and NK cells isolated from responsive patients have increased cytolytic activity compared to NK cells isolated from non-responders (Tallerico et al, 2017). A very recent study also showed that an anti-CTLA-4-EGFR immunoconjugate enhances the in vitro lysis of breast cancer cells by NK cells (Passariello et al, 2020). In B16 melanoma models, NK cells and CD8+ T cells synergistically clear tumors in response to anti-CTLA-4 and IL-2 treatment (Kohlhapp et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…antibody covalently linked to Gint4.T aptamer, thus optimizing the e cacy of the combination therapy by increasing their co-targeting at the tumor site while dispensing lower doses of either single agents and overcoming the limits related to the rapid clearance of the aptamers. We previously developed three different bispeci c conjugates consisting of EGFR aptamer linked to either anti-HER2, anti-PD-L1 or anti-CTLA-4 mAbs [38,39]. By this strategy the advantages of Gint4.T aptamer (nuclease resistance, rapid tumor uptake, durable tumor retention [31] and anti-PD-L1 antibodies (longer half-life in circulation, immunomodulatory activity) could be combined in one single molecule with improved therapeutic effectiveness and pharmacokinetic/pharmacodynamic properties over the parental moieties.…”
Section: Discussionmentioning
confidence: 99%
“…For determination of tumor cell lysis, the release of lactate dehydrogenase (LDH) in the cellular co-culture supernatants was measured by a LDH detection kit (Thermo sher Scienti c, Meridian Rd., Rockoford, IL, USA), as previously described [38,39].…”
Section: Effects Of Combinatorial Treatments On Co-cultures Of Tumor mentioning
confidence: 99%